2023
DOI: 10.7717/peerj.15245
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gut microbiota in adults with coronary atherosclerosis

Abstract: Background Cardiovascular disease, which is mainly caused by coronary atherosclerosis, is one of the leading causes of death and disability worldwide. Gut microbiota likely play an important role in coronary atherosclerosis. This study aims to investigate the microbiota profile of adults with coronary atherosclerosis to provide a theoretical basis for future research. Methods Fecal samples were collected from 35 adult patients diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…[30][31][32] Studies have concluded that the diversity of fecal bacteria is reduced or significantly altered when the host experiences pathological conditions. 30 Dramatically decreased αdiversity parameters of intestinal flora diversity were detected in various diseases, including hypertension, 33 coronary atherosclerosis, 34 and Parkinson's disease. 35 In the present study, it was observed that the αdiversity is decreased in both the Pon1 KO group and the overexpression group compared to WT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32] Studies have concluded that the diversity of fecal bacteria is reduced or significantly altered when the host experiences pathological conditions. 30 Dramatically decreased αdiversity parameters of intestinal flora diversity were detected in various diseases, including hypertension, 33 coronary atherosclerosis, 34 and Parkinson's disease. 35 In the present study, it was observed that the αdiversity is decreased in both the Pon1 KO group and the overexpression group compared to WT.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of gut bacteria has been widely considered a crucial characteristic linked to health status and multiple diseases. It has been previously reported that the stability of α‐diversity indicates a healthy status of the intestinal microbiome, and both suppressed and increased α‐diversity represents a signature of gut microbial disorders, which is frequently associated with diseases, including Pon1 ‐related diseases 30–32 . Studies have concluded that the diversity of fecal bacteria is reduced or significantly altered when the host experiences pathological conditions 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the Ruminococcus_torques group was the only shared taxon that was differentially enriched in samples from individuals with either hyperplastic polyps or conventional adenomas. Members of the Ruminococcus torques group have been positively associated with proinflammatory diets and, as also occurs with Ruminococcus gnavus (both were differentially enriched in the group with conventional adenomas), were found to be increased in several inflammatory processes and diseases [ 41 , 42 , 43 ]. Ruminococcus torques has been recently identified as a “driver” in the initiation and progression of the cancerous process [ 44 ].…”
Section: Discussionmentioning
confidence: 99%